EFFECTS OF REPETITIVE MILD TRAUMATIC BRAIN INJURY ON BEHAVIOUR OF MICE IN THE “OPEN FIELD” - Забенько Є. Ю.; Півнева Т. А. (World of Medicine and Biology, 2014)
Mild traumatic brain injury, often identified with brain concussion, is about 80% of all cases of traumatic brain injury. Due to insufficient sensitivity of standard diagnostic methods pathophysiology of mild traumatic brain injury remains poorly understood. Until recently, there was information only about external manifestations of concussion, such as loss of consciousness, amnesia, sleep disorders, emotional instability, etc. Although mild trauma is not considered to be life threatening in close perspective, the evidence of its delayed neurodegenerative effects is growing. The aim of our research was to study changes in behavior of mice after experimental repetitive mild traumatic brain injury. To induce trauma, we used a new model, developed by Michael J. Kane et al. Kane’s design represents a modification of Marmarou’s weight-drop injury. The objects were 32 males (age – 2-3 months) of white laboratory mouse (24-40 g). Animals were divided into following groups: 1) non-anesthetized, non-injured; 2) anesthetized, non-injured; 3) anesthetized, injured. Comparison of righting reflex duration in groups of anesthetized non-injured and anesthetized injured mice revealed delay in full recovery of consciousness. In the “Open field”, we tested mice for locomotor activity, rest duration, grooming activity and anxiety level on day. When conducting the test in injured animals we observed a decrease of locomotor activity and increase of anxiety level at days 5 and 10 since the first impact and recovery of respective characteristics to the level of control at day 30. Delay in recovery of consciousness together with increase of anxiety level indicate symptoms related to concussion in humans. Thus, the new model might be useful for further studies of neurodegenerative processes induced by this kind of trauma and for selection of potential treatments.
Keywords: repetitive mild traumatic brain injury; behavioral tests